Tuning the phase, morphology and size of monodisperse ScF3 and NaScF4 crystals through lanthanide doping. Issue 31 (12th July 2016) - Cao, Jingjing; Yuan, Li; Hu, Shanshan; Tang, Jianfeng; Zhou, Xianju; Yang, Jun
Abstract : The products doped with 1% Ln 3+ present diverse phase, morphologies and sizes, respectively. Abstract : Monodisperse ScF3 and NaScF4 nano-/micro-crystals were prepared by a simple solvothermal method. There were many important factors including the molar ratio of Na/F/(Sc + Ln) and Ln 3+ doping to control the synthesis of the products. A phase transformation from monoclinic ScF3 to hexagonal NaScF4 was observed with different molar ratios of Na/F/Sc. Herein, the products doped with 1% Ln 3+ (La–Lu, except Pm) demonstrated abundant phases, morphologies and sizes. Moreover, the products with different Lu 3+ doping concentrations from 1% to 60% were prepared. The results revealed that different kinds of 1% Ln 3+ (La–Lu, except Pm) and diverse concentrations of Lu 3+ can modify the phase, morphology and size of the prepared products. A possible formation mechanism for the products with diverse morphologies is proposed. In addition, Ln 3+ -doped ScF3 or NaScF4 nano-/micro-crystals presented characteristic up/down-conversion fluorescence spectra.